Smart Lighting System for Vocational Campus Workshop Environment - Ahmad Darmawi; Hasna Khairunnisa; Dedy Harianto; Agus Ardiyanto (LPPM Institut Teknologi Adhi Tama Surabaya (ITATS), 2025)
AK-Tekstil Solo is a vocational campus with several workshops for lectures, one of which is the Spinning and Weaving Workshop. It has yarn and fabric manufacturing machines and holds the most significant electricity consumption for machine operations, lighting, and other instruments. Hence, a smart workshop room with electrical energy efficiency is crucial. This research aims to design and develop a smart workshop lighting system using an Arduino-based microcontroller circuit and photocell components. The light intensity setting system is performed by determining the measurement point of light intensity and measuring the natural and artificial light intensity as the input for photocell and relay. An automated lighting system for the smart workshop was then developed using a photocell censor based on the Arduino Mega microcontroller. Product testing shows that the automatic switches and relays based on programming successfully work the automated system.